2010
DOI: 10.1593/neo.10568
|View full text |Cite
|
Sign up to set email alerts
|

Replication Timing Aberrations and Aneuploidy in Peripheral Blood Lymphocytes of Breast Cancer Patients

Abstract: The HER2 and CEN17 aberrant replication differentiated clearly between BCA patients and control subjects. Thus, monitoring the replication of these genes offers potential blood markers for the detection and monitoring of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Surprisingly, the asynchronous replication pattern observed in cancer patients is not restricted to tumor tissue but also occurs in noncancerous cells as well [66,67,68,69,70]. This is best exemplified by the presence of aberrant asynchronous replication between alleles in the peripheral lymphocytes of individuals with solid tumors [66,67].…”
Section: Dna Replication Timing and The Evolution Of The Cancer Gementioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, the asynchronous replication pattern observed in cancer patients is not restricted to tumor tissue but also occurs in noncancerous cells as well [66,67,68,69,70]. This is best exemplified by the presence of aberrant asynchronous replication between alleles in the peripheral lymphocytes of individuals with solid tumors [66,67].…”
Section: Dna Replication Timing and The Evolution Of The Cancer Gementioning
confidence: 99%
“…Interestingly, this altered replication-timing pattern is present in pre-malignant cells, in individuals pre-disposed to cancer, and in individuals living in polluted areas with a high likelihood of getting cancer, suggesting that this may be an early event during carcinogenesis [63,65,67,72]. The replication asynchrony observed in cancerous tissue and normal cells in individuals with cancer is generally a result of the earlier replication of one of the alleles [67,70,72], however, in some cases the delayed replication of one allele has been detected [71]. This aberrant asynchronous replication is heritable (i.e.…”
Section: Dna Replication Timing and The Evolution Of The Cancer Gementioning
confidence: 99%
See 1 more Smart Citation
“…Based on Mendelian genetics, mammals receive two alleles of each gene from their parents. Both alleles are regulated symmetrically with respect to expression activity, and replication is synchronous, such as in the case of the genes TP53, RB1, AML1, HER2, and C-MYC (Hiratani and Gilbert, 2009;Grinberg-Rashi et al, 2010). However, monoallelically expressed genes are also found in the genome, in which the replication of the DNA of the two alleles is asynchronous, such as in SNRPN (Hiratani and Gilbert, 2009;Grinberg-Rashi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown the known monoallelically expressed genes are nonsynchronous (Hiratani and Gilbert, 2009;Grinberg-Rashi et al, 2010). These genes include the following examples: 1) imprinted genes, particularly the Prader-Willi/Angelman syndrome gene SNRPN; the paternal allele replicates earlier than the maternal allele (Knoll et al, 1994;Gunaratne et al, 1995;Simon et al, 1999); 2) genes on the inactive X chromosome in females (Boggs and Chinault, 1994); and 3) exclusively biallelic genes (Mostoslavsky et al, 2001).…”
Section: Introductionmentioning
confidence: 99%